Characterization of nurse staffing who are away from work due to musculoskeletal disorders in a university hospital - Yuri Marques Souza; Daiane Dal Pai; Larissa Martini Junqueira; Andréia Barcellos Teixeira Macedo; Juliana Petri Tavares; Eunice Beatriz Martin Chaves (Universidade Federal de Santa Maria, 2020)
Objective: To describe the sociodemographic and occupational characteristics of nurse staffing from an university hospital who are away from work due to musculoskeletal cumulative disorders and the association with absenteeism time. Method: retrospective, analytic and cross-sectional study. Medical records from 2012 to 2017 were analyzed from medical records of workers using descriptive and analytical statistics. Results: Out of 2,761 recorded absences from nurse staffing, 449 referred to musculoskeletal disorders (16.26%), the highest percentage due to back pain (41.5%) and 78 workers had psychiatric diagnosis, especially depression (43.4%). There was identified in the group with longer time of absence (> 15 days) the predominance of the category of nursing assistants and technicians (p = 0.006), with lower median age (p = 0.021) and higher education (p = 0.035). Conclusion: The elevated number of absences due to musculoskeletal disorders, sometimes associated with other comorbidities, requires follow-up and prevention in the workplaces.